Decarbonising Transport – The Spatial Effects of Railway Container Transport on Carbon Emissions - BAI, Zhizhen; LI, Xiaodong; KUANG, Haibo (Promet - Traffic&Transportation, 2026)
China is advancing a strategic transport shift to establish railway container transport as a key logistics pillar, supporting its dual carbon goals through sector restructuring. However, empirical research on its low-carbon efficacy remains limited. Based on the spatial Dobbin model, and combining the data from railway container loading and unloading stations, night lighting and socio-economic factors, this study deeply studies the remarkable characteristics of regional changes of railway container transportation and carbon emissions in China, and comprehensively discusses how railway container transportation affects regional carbon emissions at different scales. Key findings: (1) Urban carbon emissions are rising, with eastern cities emitting most intensely and western regions showing widespread high emissions. Railway container flows exhibit spatial disparities, creating “oligarchic cities” with concentrated transport activity. (2) Railway container transportation notably curbs the production of carbon emissions, thereby facilitating the attainment of regional low-carbon objectives. Moreover, when comparing across regions, the suppressive impact of railway container transportation on carbon emissions stands out more prominently in both the eastern and western regions. The railway container transportation conducted in the Yangtze River Delta Economic Zone and the Bohai Rim Economic Zone demonstrates a more pronounced suppressive effect on regional carbon emissions.